(untitled) (The Strategic Review for Southern Africa, 2020)
This article explores the meaning of peace and human security from theperspective of the individual — the presumed referent point of security— and examines responses to armed conflict, a leading source of insecurity for African peoples. It identifies inherent flaws in approaches to conflict in Africa and looks to a different field — that of leadership — for a more effective formula for peacemaking. In the absence of a framework that can effectively end the cycle of conflict relapse in Africa,the paper argues that an alternative framing of leadership is needed; and that alternative leadership approaches to dealing with conflict andinsecurity offer a chance for stable peace and human security. It suggests that an expanded perspective on leadership provides a basis for exploring interventions that can potentially alter peacemaking discourses as well as the terrain in which peacemaking takes place. The article therefore asks what a focus on the individual as the referent point of security means if and when viewed from the perspective of a collection of individuals. In this regard, it presents emerging perspectives from a study of young Africans on leadership programmes in a classroom setting and attempts to extrapolate them to wider societal settings. It then explores how a different perspective of leadership might serve as a facilitator of peace and human security in Africa, drawing examples from past and on-going situations of armed conflict in Africa.